IDENTIFIKASI PERMASALAHAN KELOMPOK USAHA BERSAMA (KUBE) DALAM PROGRAM PENGENTASAN KEMISKINAN DI SUMATERA BARAT - Yulia Anas (Universitas Negeri Padang, 2014)
This study aims to identify problems Business Group (KUBE) in poverty alleviation programs in West Sumatra. By using descriptive qualitative research methods, the study was conducted in Tanah Datar and Pasaman West with different programs are KUBE breeders and Fishermen. Based on the results we can see that the main problem KUBE in poverty alleviation program starts from the formation of KUBE, institutional aspects of the problem, social and economic aspects. It is estimated this to be the cause of failure of the program in poverty reductionKeywords : program in poverty reduction, KUBE, Problem of KUBE